The use of inquiry methods in the study of intermolecular forces effects between liquid molecules via VPBP kit / Mimi Azarina Ahmad Barai ... [et al.] - Ahmad Barai, Mimi Azarina; Jamali, Amal Hayati; Ping, Chia Chew; Amir Mizan, Mardiana (2020)
Learning the effect of intermolecular forces on vapour pressure and boiling point of liquids among students in Matriculation Programme. The difficulties to understand the abstract concepts is related to the students' ability to visualize the phenomena. Therefore, it is important to address those problems and challenges with the right approach. The purpose of this study is to improve the students' understanding of the concepts through discovery inquiry method by utilizing the VPBP kit as a learning tool. The research use the 5E discovery inquiry approach which involving five phases, namely: engage, explore, explain, elaborate and evaluate. There were 38 science stream students from two different Matriculation College were selected as respondents. Group A from Kolej Matrikulasi Selangor and Group B from Kolej Matrikulasi Negeri Sembilan. Students were taught the relationship of intermolecular forces with vapour pressure and boiling point of a liquid during tutorial session. After the lesson, students were required to construct the concepts of vapour pressure and boiling point of liquids and gaseous state by using the VPBP kit with reference to different strength of intermolecular forces. Quantitative data were collected through pre-test and post-test and were analyzed by percentage. The analysis of results showed that there was a significant difference in students' performance with percentage increase up to 81.1% for group A and 57.8% for group B. Based on these findings, using discovery inquiry method enhancing students' understanding to describe the intermolecular forces on vapour pressure and boiling point.